CHALLENGES AND ACHIEVEMENTS OF E-EDUCATION - Ibrohimova, Marhabo Ulugbek kizi; Shukurova, Shokhsanam Kakhramon kizi (INTERNATIONAL CONFERENCES, 2022)
In this article, you can find the necessary information about e-learning in foreign countries. There is data about the problems you might face during online learning and what it has succeeded at in the education system. I have given some life experiences for that to be easier and brighter to understand; meanwhile, catch up with the real meaning and value.